2011
DOI: 10.1021/es103779h
|View full text |Cite
|
Sign up to set email alerts
|

TiO2 Nanoparticles in the Marine Environment: Impact on the Toxicity of Tributyltin to Abalone (Haliotis diversicolor supertexta) Embryos

Abstract: Little information is available on the potential ecotoxicity of manufactured nanomaterials (MNMs) in the marine environment. To carefully address this issue, the toxicity of nanosized titanium dioxide (nTiO(2)) aggregates in the marine environment was evaluated using abalone (Haliotis diversicolor supertexta) embryonic development as a model. The effect of nTiO(2) aggregates on the toxicity of the highly toxic marine antifouling compound tributyltin (TBT) to abalone embryos was also investigated. No developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
90
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(96 citation statements)
references
References 29 publications
6
90
0
Order By: Relevance
“…22 The tributyltin/nano-TiO 2 adduct is more toxic to abalone embryos than tributyltin alone. 23 Similar synergistic toxicities to aquatic organisms have also been found for As, Pb, Cu, and Cd in the presence of nano-Al 2 O 3 , nanoFe 2 O 3 , and nano-TiO 2 . 24−28 Recently, we have observed significant research efforts exerted toward the investigation of nanoparticle toxicity.…”
Section: ■ Introductionsupporting
confidence: 54%
“…22 The tributyltin/nano-TiO 2 adduct is more toxic to abalone embryos than tributyltin alone. 23 Similar synergistic toxicities to aquatic organisms have also been found for As, Pb, Cu, and Cd in the presence of nano-Al 2 O 3 , nanoFe 2 O 3 , and nano-TiO 2 . 24−28 Recently, we have observed significant research efforts exerted toward the investigation of nanoparticle toxicity.…”
Section: ■ Introductionsupporting
confidence: 54%
“…In contrast, several previous studies have reported enhanced bioavailability of organic toxicants to exposure organisms (e.g., tributyltin, BDE-209, DDT, TCDD) in the presence of n-TiO 2 [12,13,45,46], as n-TiO 2 acted as a carrier that enables compounds to adsorb on the organism surface. At the same time, adsorption and sedimentation also normally occurred in organic toxicants with n-TiO 2 in exposure media [12,46,51]. Thus, sedimentation does not appear to be the major reason that affects the bioavailability of organic toxicants by organisms.…”
Section: Discussionmentioning
confidence: 76%
“…Previous studies have reported that n-TiO 2 can adsorb heavy metals [4,34,44] or organic toxicants, including tributyltin, PBDEs, DDT and tetrachlorodibenzo-p-dioxin [TCDD] [12,13,45,46], while study showed the aggregation and subsequent sedimentation of nTiO 2 with tributyltin [12]. At the same time, we did not measure and (E) GSH content in larvae after exposure to PCP alone (0, 3, 10, and 30 g/L) and in the presence of n-TiO2 (0.1 mg/L) for 6 days.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations